2015
DOI: 10.1016/j.bbamcr.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Hsf4 counteracts Hsf1 transcription activities and increases lens epithelial cell survival in vitro

Abstract: The interplay between Hsf4 and Hsf1 plays an important role in the regulation of lens homeostasis. However, the mechanism of the intermolecular association involved is still unclear. In this paper, we find that reconstitution of Hsf4b into Hsf4-/- lens epithelial (mLEC/Hsf4-/-) cells can simultaneously downregulate Hsp70 expression and upregulate the expression of small heat shock proteins Hsp25 and αB-crystallin at both RNA and protein levels. ChIP assay results indicate Hsf4b, which binds to the promoters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Co‐immunoprecipitation (CoIP) was carried out as previously described . 1 mg of cell lysate was treated with protein A/G agarose beads for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Co‐immunoprecipitation (CoIP) was carried out as previously described . 1 mg of cell lysate was treated with protein A/G agarose beads for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…High glucose-induced oxidative stress is an important cause of diabetic cataract [2]. The human lens epithelial cell line (HLEB3) was widely used to do research [13][14][15]. Here, using the lens epithelial cell line, we found that high glucose can directly induce the oxidative stress and cell apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Further investigation revealed that residue K206 was a key site for HSF4 ubiquitination. It was showed that the HRA/B domain could mediate the interaction between HSF1 and other factors (Cui et al, 2015;Hu and Mivechi, 2011). Herein, we have shown that the HRA/B domain (130-203) of HSF4 is indispensable for the interaction of HSF4 with BCAS2.…”
Section: Discussionmentioning
confidence: 91%